Advanced financial accounting - Baker, Richard E. (McGraw-Hill/Irwin, 2008)
The seventh edition of Advanced Financial Accounting is a comprehensive and highly illustrated presentation of the accounting and reporting principles used in a variety of business entities. The complete presentations of worksheets, schedules, and financial statements allow students to see the development of each new topic. The book's building block approach introduces concepts with simple examples and then gradually introduces complexity, allowing students to easily keep pace with the material. Because the course often serves students who plan to take the CPA exam, much of Advanced Financial Accounting's end-of-chapter material is provided in the formats as tested on the CPA exam. A wide variety of multiple-choice questions, cases requiring written presentations, and other objective answer format materials helps students even further to reinforce their mastery of text concepts